Solstice - Hoover, P. J. 1970- (Patricia J.) (New York : Tor Teen, a Tom Doherty Associates Book, 2013)
Eighteen-year-old Piper lives with her controlling mother amid a Global Heating Crisis, but when she gets her first taste of freedom she discovers a universe of gods and monsters where her true identity, kept secret from her birth, could make all the difference in the world.
Keywords: Global warming -- Fiction; Identity -- Fiction; Mothers and daughters -- Fiction; Love -- Fiction; Persephone (Greek deity) -- Fiction; Goddesses, Greek -- Fiction; Gods, Greek -- Fiction; Mythology, Greek -- Fiction; JUVENILE FICTION / Fantasy & Magic; JUVENILE FICTION / Love & Romance